TRAUMATIC GASTRIC RUPTURE FOLLOWING BLUNT TRAUMA ABDOMEN: A Case Series - Hota, P. K.; Babu, M.; Satyam, G.; Praveen,; Ch. (BALI MEDICAL JOURNAL, 2014)
Background: Gastric rupture following blunt injury abdomen is a rare presentation with a reported incidence of 0.02-1.7% in current literature. History of recent meal has been implicated in traumatic gastric rupture. Commonly traumatic gastric rupture is associated with other injuries like splenic injury and fractures. Prompt diagnosis and early intervention reduces mortality and morbidity. Primary two layered closure can be done for a better surgical outcome. We report 2 cases of blunt injury abdomen with gastric rupture, one with road traffic accident and other being from a fall from a height, which were managed successfully without any post operative morbidity and mortality.